MODERN PECULIARITIES OF IXODIC TICK-BORNE BORRELIOSIS EPIDEMIOLOGY IN KEMEROVO REGION - Анна Роняевна Ефимова; Ольга Михайловна Дроздова (Медицина в Кузбассе, 2016)
The study long-term dynamics of Lyme Borreliosis incidence within the territory of Kemerovo region since 1993 to 2015 years. Borrelia DNA has been detected in a ticks picked in the wild and removed from affected civilians. Objective – to establish the epidemiologic patterns of Lyme Borreliosis spread in the Kemerovo region. Methods. Retrospective epidemiological analysis, enzyme immunoassay (ELISA), polymerase chain reaction and different statistics. Results. Epidemiological pattern of ixodic tick-borne borreliosis spread in the territory of the Kemerovo region has been investigated. High incidence of the disease with the trend to increasing has been detected. Maximum incidence was registered among the rural population and citizens aged over 41. Northern areas of the region were noted for high bitings occurrence, abundance and contamination of Ixodes ticks. Borrelia DNA was detected in 35,46 ± 6,26 % ticks. Conclusions. Ixodic tick-borne borreliosis incidence rate, bitings occurrence and contaminated ticks percentage differ considerably in different areas of the region, which determines a differentiated approach to preventive measures arrangement.